Alpha-cell paracrine signaling in the regulation of beta-cell insulin secretion - Holter, Marlena M.; Saikia, Mridusmita; Cummings, Bethany P. (Frontiers in Endocrinology, 2022)
As an incretin hormone, glucagon-like peptide 1 (GLP-1) lowers blood glucose levels by enhancing glucose-stimulated insulin secretion from pancreatic beta-cells. Therapies targeting the GLP-1 receptor (GLP-1R) use the classical incretin model as a physiological framework in which GLP-1 secreted from enteroendocrine L-cells acts on the beta-cell GLP-1R. However, this model has come into question as evidence demonstrating local, intra-islet GLP-1 production has advanced the competing hypothesis that the incretin activity of GLP-1 may reflect paracrine signaling of GLP-1 from alpha-cells on GLP-1Rs on beta-cells. Additionally, recent studies suggest that alpha-cell-derived glucagon can serve as an additional, albeit less potent, ligand for the beta-cell GLP-1R, thereby expanding the role of alpha-cells beyond that of a counterregulatory cell-type. Efforts to understand the role of the alpha-cell in the regulation of islet function have revealed both transcriptional and functional heterogeneity within the alpha-cell population. Further analysis of this heterogeneity suggests that functionally distinct alpha-cell subpopulations display alterations in islet hormone profile. Thus, the role of the alpha-cell in glucose homeostasis has evolved in recent years, such that alpha-cell to beta-cell communication now presents a critical axis regulating the functional capacity of beta-cells. Herein, we describe and integrate recent advances in our understanding of the impact of alpha-cell paracrine signaling on insulin secretory dynamics and how this intra-islet crosstalk more broadly contributes to whole body glucose regulation in health and under metabolic stress. Moreover, we explore how these conceptual changes in our understanding of intra-islet GLP-1 biology may impact our understanding of the mechanisms of incretin-based therapeutics.